Bond softness sensitive bond-valence parameters for crystal structure plausibility tests - Chen, Haomin; Adams, Stefan (IUCrJ, 2017)
Based on a description of bond valence as a function of valence electron density, a systematic bond softness sensitive approach to determine bond-valence parameters and related quantities such as coordination numbers is elaborated and applied to determine bond-valence parameters for 706 cation–anion pairs. While the approach is closely related to the earlier softBV parameter set, the new softNC1 parameters proposed in this work may be simpler to apply in plausibility checks of crystal structures, as they follow the first coordination shell convention. The performance of this softNC1 bond-valence parameter set is compared with that of the previously derived softBV parameter set that also factors in contributions from higher coordination shells, and with a benchmarking parameter set that has been optimized following the conventional choice of a universal value of the bond-valence parameter b . The results show that a systematic adaptation of the bond-valence parameters to the bond softness leads to a significant improvement in the bond-valence parameters, particularly for bonds involving soft anions, and is safer than individual free refinements of both R 0 and b from a limited number of reference cation environments.